RESPONSE AND STRATEGY FOR HANDLING FLASH FLOODS AND LANDSLIDES IN BENER MERIAH AND TAKENGON: A CASE STUDY OF AID FROM THE IAEB - Muammar Khaddafi; Chalirafi; Hendra Harmain; Mohd Idris Dalimunthe; Alistraja Dison Silalahi (International Review of Practical Innovation, Technology and Green Energy (IRPITAGE), 2025)
This study aims to understand the responses, strategies, constraints, and roles of communities in managing flash floods and landslides in Bener Meriah and Takengon Regencies. Using a qualitative approach with a case study design, data were collected through in-depth interviews, participant observation, and secondary documents. Analysis was conducted thematically to identify patterns, themes, and meanings of disaster management practices in the field. The results show that this disaster caused multidimensional impacts, including loss of life, mass displacement, and damage to critical infrastructure. The IAEB and related institutions implemented a priority needs-based strategy, cross-institutional collaboration, utilization of GIS technology, and social and infrastructure rehabilitation. The main constraints included limited access, resources, coordination, and the psychosocial conditions of the affected communities. Synergy between the IAEB and local communities through community-based emergency response groups proved effective in accelerating recovery and reducing disaster risk. This study emphasizes the importance of an integrated, participatory, and needs-based approach in increasing regional resilience to disasters.